The Smc5/6 complex regulates the yeast Mph1 helicase at RNA-DNA hybrid-mediated DNA damage - Lafuente-Barquero, Juan; Luke-Glaser, Sarah; Luke, Brian (PLoS Genetics, 2017)
RNA-DNA hybrids are naturally occurring obstacles that must be overcome by the DNA replication machinery. In the absence of RNase H enzymes, RNA-DNA hybrids accumulate, resulting in replication stress, DNA damage and compromised genomic integrity. We demonstrate that Mph1, the yeast homolog of Fanconi anemia protein M (FANCM), is required for cell viability in the absence of RNase H enzymes. The integrity of the Mph1 helicase domain is crucial to prevent the accumulation of RNA-DNA hybrids and RNA-DNA hybrid-dependent DNA damage, as determined by Rad52 foci. Mph1 forms foci when RNA-DNA hybrids accumulate, e.g. in RNase H or THO-complex mutants and at short telomeres. Mph1, however is a double-edged sword, whose action at hybrids must be regulated by the Smc5/6 complex. This is underlined by the observation that simultaneous inactivation of RNase H2 and Smc5/6 results in Mph1-dependent synthetic lethality, which is likely due to an accumulation of toxic recombination intermediates. The data presented here support a model, where Mph1’s helicase activity plays a crucial role in responding to persistent RNA-DNA hybrids.